Sodium-ion battery hard carbon negative electrode material, preparation method thereof and sodium-ion battery negative electrode
By pretreating the hard carbon carbon source with Na3PO4 and NaOH mixed solution, the low ion transfer rate and impurities of the hard carbon negative electrode material of sodium ion battery are solved, and the high first-round efficiency, capacity and rate performance are improved.
Patent Information
- Application Number
- CN202411430727.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
AI Technical Summary
The hard carbon anode material of sodium ion battery has problems such as low ion transfer rate, many impurities of biomass raw materials and difficulty in ensuring stability, and the rate performance needs to be improved.
The hard carbon carbon source is pretreated by a mixed solution of Na3PO4 and NaOH. The Na+ filling in the solution and doping of P heteroatoms, surface impurities are removed and Na+ defects are formed, thereby increasing the Na+ transfer rate.
The first-round efficiency and capacity of hard carbon anode material is improved, the rate-to-rate performance is enhanced, and the hard carbon anode material of sodium ion battery with high first-round efficiency and capacity and high rate-to-rate performance is obtained.
Smart Images

Figure CN119503764A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a sodium ion battery hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery negative electrode. Background Art
[0002] Lithium-ion batteries have high specific capacity, long cycle life and stable operation, and have attracted much attention in recent decades. However, due to limited lithium resources, lithium-ion batteries are difficult to meet the growing needs of electric vehicles and energy storage development. Sodium resources are abundant in the earth's crust, so sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries. The negative electrode material is one of the most important components of the battery. The most commonly used graphite negative electrode material for lithium-ion batteries is not suitable for sodium-ion batteries. Hard carbon is currently the negative electrode material with the best comprehensive electrochemical performance for sodium-ion batteries and has been widely used in sodium-ion batteries. As a sodium-ion negative electrode material, hard carbon has the advantages of abundant raw materials, stable structure, low voltage platform and excellent safety performance. However, there are also problems such as low ion transfer rate and many impurities in biomass raw materials that make it difficult to ensure stability, and the rate performance needs to be improved. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings, one of the objects of the present invention is to provide a method for preparing a hard carbon negative electrode material for a sodium ion battery, which can obtain a hard carbon negative electrode material for a sodium ion battery with high first-cycle efficiency and capacity and high rate performance.
[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0005] A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0006] S1, prepare a mixed solution of Na3PO4 and NaOH;
[0007] S2, pretreating the hard carbon source with the mixed solution,
[0008] S3, solid-liquid separation, washing the pretreated hard carbon source with a washing liquid until the washing liquid is neutral;
[0009] S4. The washed hard carbon source is subjected to high-temperature pyrolysis to obtain a hard carbon negative electrode material.
[0010] Furthermore, in step S1, in the mixed solution, the concentration of Na3PO4 is 0.1-0.5 mol / L, and the concentration of NaOH is 0.5-3 mol / L.
[0011] Exemplarily, the concentration of Na3PO4 is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L or a range consisting of any two thereof, and the concentration of NaOH is 0.5mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L, 2.5mol / L, 3mol / L or a range consisting of any two thereof.
[0012] Furthermore, the hard carbon source is preliminarily carbonized coconut shell biomass.
[0013] Furthermore, in step S2, the pretreatment temperature is 30 to 100°C, and the pretreatment time is 2 to 24 hours.
[0014] Illustratively, the pretreatment temperature is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or a range consisting of any two thereof.
[0015] Furthermore, in step S2, the mass ratio of NaOH to the initially carbonized coconut shell biomass is 0.08-0.5:1, and the mass ratio of Na3PO4 to the initially carbonized coconut shell biomass is 0.08-0.5:1.
[0016] Furthermore, the washing liquid is deionized water or pure water.
[0017] Further, the high temperature pyrolysis temperature is 900-1500°C, the time is 2-6h, and the heating rate is 1-5°C / min. Exemplarily, the high temperature pyrolysis temperature is 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a range consisting of any two thereof; the heating rate is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range consisting of any two thereof.
[0018] Furthermore, nitrogen or argon is used as a protective gas throughout the high-temperature pyrolysis process.
[0019] A sodium ion battery hard carbon negative electrode material is prepared by the preparation method as described above.
[0020] A sodium ion battery negative electrode comprises the sodium ion battery hard carbon negative electrode material as described above.
[0021] The beneficial effects of the present invention are:
[0022] 1) The present invention uses a mixed solution of Na3PO4 and NaOH to treat coconut shell carbon precursor. Na3PO4 is easily hydrolyzed into NaOH and Na2HPO4 (Na3PO4+H2O→NaOH+Na2HPO4) when it comes into contact with water. Impurities in the biomass raw materials (silicon is the main impurity) react and dissolve under the action of alkali, and the corresponding vacancies are replaced by the rich Na + At the same time, the P heteroatom provided by Na2HPO4 is also doped into the carbon skeleton. Therefore, the coconut shell hard carbon was pre-treated with a mixed solution of NaOH and Na3PO4 to effectively remove its surface impurities and form Na + Vacancy defects and successful doping with P heteroatoms.
[0023] 2) The removal of surface impurities effectively improves the first cycle efficiency and capacity of hard carbon, and the Na + Defects and P heteroatom doping structures enhance the Na + The transmission rate is increased, and the rate performance of the hard carbon negative electrode is improved, thus obtaining a sodium ion battery hard carbon negative electrode material with high first-cycle efficiency and capacity as well as high rate performance.
[0024] 3) The preparation method is simple and easy to operate, and the pretreated alkali solution raw materials Na3PO4 and NaOH are easily available, which is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 It is a comparison diagram of the first cycle charge and discharge curves of Example 1 of the present invention and Comparative Example 1;
[0028] Figure 2 It is a comparison diagram of the cycle curves of Examples 1-7 and Comparative Example 1;
[0029] Figure 3 It is a comparison diagram of the rate curves of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0031] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0032] A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:
[0033] S1. Prepare a mixed solution of Na3PO4 and NaOH; in the mixed solution, the concentration of Na3PO4 is 0.1-0.5 mol / L, and the concentration of NaOH is 0.5-3 mol / L.
[0034] S2. Use the mixed solution to treat the hard carbon source, which is preliminarily carbonized coconut shell biomass purchased from Suzhou Yituo Lian International Trade Co., Ltd. The specific steps are: place the mixed solution and 50g of preliminarily carbonized coconut shell biomass in a 500mL beaker, stir the reaction at 30-100°C for 2-24h. By weight, in the reaction solution, the mass ratio of NaOH to preliminarily carbonized coconut shell biomass is 0.08-0.5:1, and the mass ratio of Na3PO4 to preliminarily carbonized coconut shell biomass is 0.08-0.5:1.
[0035] S3, solid-liquid separation, and washing the pretreated hard carbon source with a washing liquid until the washing liquid is neutral; after the reaction is completed, a vacuum filter is used to separate the solid and liquid and the precursor is washed with a washing liquid until the washing liquid is neutral; the precursor is placed in a forced air drying oven and dried at 80°C.
[0036] The washing liquid is deionized water or pure water.
[0037] S4. The washed precursor is subjected to high-temperature pyrolysis to obtain a hard carbon negative electrode material.
[0038] The high-temperature pyrolysis specifically includes the following process: placing the treated precursor in a corundum crucible, transferring the corundum crucible to a tubular furnace, heating to 900-1500°C at a rate of 1-5°C / min, reacting for 2-6 hours, and then naturally cooling to room temperature. Nitrogen or argon is used as a protective gas throughout the reaction.
[0039] A method for preparing a sodium ion battery containing the hard carbon negative electrode comprises the following steps:
[0040] Step 1: Mix the obtained hard carbon negative electrode material with the conductive additive and the binder to prepare a slurry, and use water as a dispersant. When preparing the slurry, in order to evenly mix the components, a mixer is preferably used for sufficient mixing.
[0041] In some embodiments, the conductive additive is selected from at least one of carbon black, acetylene black, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene; the mass ratio of the conductive additive to the negative electrode active material is 1 to 10 w.t.%.
[0042] In some embodiments, the binder is selected from at least one of sodium alginate, acrylic resin PAA, lithium polyacrylate LiPAA, sodium polyacrylate NaPAA, carboxymethyl cellulose CMC / styrene butadiene rubber SBR. The mass ratio of the binder to the negative electrode active material is 1 to 10 w.t.%.
[0043] Step 2: Use a coating machine to coat the obtained slurry on a copper foil current collector with a thickness of 4 to 15 μm, dry it, roll it, and cut it into appropriate sizes for later use.
[0044] Step 3: The positive electrode is prepared by a slurry coating process similar to that of the negative electrode. The positive electrode material includes one or more of the following substances:
[0045] a. sodium-containing transition metal oxides, such as NaMO2 (M is one or more transition metal elements);
[0046] b. Polyanion cathode materials, such as Na x M y (X a O b ) z Z w (M is a transition metal atom, X is phosphorus, sulfur or tungsten, and Z is F or OH), which is connected by polyanion polyhedrons and transition metal ion polyhedrons through strong covalent bonds and has a strong and open three-dimensional network structure;
[0047] c. Prussian blue / white, its chemical formula is Na xM1[M2(CN)6] (M is a transition metal atom, such as Mn, Ni, Co, Zn, Cu and Fe, etc., 0<x≤2). It is divided into two materials, Prussian white (high) and Prussian blue (low), according to the sodium ion content. It is a new technology route for sodium ion batteries.
[0048] The positive electrode current collector generally uses aluminum, nickel, stainless steel, titanium, etc. or a composite foil formed by metal and non-metal. The coating dispersion solvent generally uses a non-aqueous solvent, and the adhesive generally uses a fluorine-containing polymer, such as polyvinylidene fluoride (PVDF).
[0049] Step 4: Assemble the negative electrode sheet, separator and positive electrode into a battery.
[0050] Step 5: Add electrolyte and then seal to obtain a sodium battery.
[0051] The electrolyte system is a non-aqueous electrolyte solution containing salts that is liquid at room temperature. The aprotic solvent used in the electrolyte includes at least one of dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (VC), fluoroethylene carbonate (FEC), and ethyl methyl carbonate (EMC), and at least one sodium-containing electrolyte salt that can be dissolved in the above solvents, such as sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), etc.
[0052] The concentration of the electrolyte solution is preferably 0.8 to 2.0 mol / L.
[0053] In some embodiments, 0.1 to 3 wt.% of a compound containing a carboxylic anhydride group, a compound containing sultones (such as propene sultone, propane sultone, etc.) or a compound containing boron is added to the electrolyte to improve the chemical stability of the electrolyte and inhibit its decomposition on the surface of the negative electrode material.
[0054] In some embodiments, the electrolyte system includes some or all solid electrolyte components, such as an organic solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, etc.
[0055] Example
[0056] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0057] Example 1
[0058] S1. Prepare a mixed solution of Na3PO4 and NaOH; in the mixed solution, the concentration of Na3PO4 is 0.2 mol / L, and the concentration of NaOH is 1.5 mol / L.
[0059] S2. Mix 50g of the initially carbonized coconut shell biomass precursor with 200mL of a mixed solution of 1.5mol / L NaOH and 0.2mol / L Na3PO4 in a 500mL beaker. Then add a magnet and place the reaction system on a magnetic stirrer to react at a reaction temperature of 75°C for 24h. In the reaction solution, the mass of NaOH is 1.5*200 / 1000*40=12g, and the mass ratio of NaOH to the initially carbonized coconut shell biomass is 12:50=0.24:1; the mass of Na3PO4 is 0.2*200 / 1000*164=6.56g, and the mass ratio of NaOH to the initially carbonized coconut shell biomass is 6.56:50=0.13:1;
[0060] S3. After the reaction is completed, a vacuum filter is used to separate the solid and liquid and the precursor is washed with deionized water until the filtrate is neutral. After the above steps are completed, the precursor is placed in a forced air drying oven and dried at 80°C.
[0061] S4. Place the treated precursor in a corundum crucible, then transfer the corundum crucible to a tubular furnace, use nitrogen as a protective gas throughout the process, heat the temperature to 1400°C at a heating rate of 5°C / min, keep the temperature for 2h, and then cool naturally to room temperature to obtain a hard carbon negative electrode material.
[0062] Example 2
[0063] Example 2 is basically the same as Example 1, the main difference being that the concentration of NaOH is 1 mol / L, and the other experimental conditions remain unchanged.
[0064] Example 3
[0065] Example 3 is basically the same as Example 1, the main difference being that the concentration of NaOH is 0.5 mol / L, and the other experimental conditions remain unchanged.
[0066] Example 4
[0067] Example 4 is basically the same as Example 1, the main difference being that the processing temperature of the precursor in Example 4 is changed from 75° C. to 30° C., and the other experimental conditions remain unchanged.
[0068] Example 5
[0069] Example 5 is basically the same as Example 1, the main difference being that the precursor treatment time in Example 5 is 3 h, and the other experimental conditions remain unchanged.
[0070] Example 6
[0071] Example 6 is basically the same as Example 1, the main difference being that the pyrolysis temperature of the precursor during pyrolysis in Example 6 is 1500° C. The other experimental conditions remain unchanged.
[0072] Example 7
[0073] Example 7 is substantially the same as Example 1, the main difference being that the holding time during the precursor pyrolysis process in Example 7 is 3 hours, and the other experimental conditions remain unchanged.
[0074] Example 8
[0075] Example 8 is basically the same as Example 1, the main difference being that the concentration of NaOH is 3 mol / L, and the other experimental conditions remain unchanged.
[0076] Example 9
[0077] Example 9 is basically the same as Example 1, the main difference being that the concentration of Na3PO4 is 0.1 mol / L, and the other experimental conditions remain unchanged.
[0078] Example 10
[0079] Example 10 is basically the same as Example 1, the main difference being that the concentration of Na3PO4 is 0.5 mol / L, and the other experimental conditions remain unchanged.
[0080] Comparative Example 1
[0081] The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the precursor treatment processes S1 to S3 are removed, and the hard carbon negative electrode material is directly prepared by high-temperature pyrolysis of carbonized coconut shell biomass.
[0082] Comparative Example 2
[0083] Comparative Example 2 is substantially the same as Example 1, the main difference being that the concentration of NaOH is 0.3 mol / L, and the other experimental conditions remain unchanged.
[0084] Comparative Example 3
[0085] Comparative Example 3 is substantially the same as Example 1, the main difference being that the concentration of NaOH is 5 mol / L, and the other experimental conditions remain unchanged.
[0086] Comparative Example 4
[0087] Comparative Example 4 is substantially the same as Example 1, the main difference being that the concentration of Na3PO4 is 0.05 mol / L, and the other experimental conditions remain unchanged.
[0088] Comparative Example 5
[0089] Comparative Example 5 is substantially the same as Example 1, the main difference being that the concentration of Na3PO4 is 0.7 mol / L, and the other experimental conditions remain unchanged.
[0090] Experimental Example 1
[0091] The physical and chemical properties of the hard carbon negative electrode materials prepared in Examples 1-10 and Comparative Examples 1-5 were tested, and the test results are shown in Table 1.
[0092] Specific surface area test method: measure the amount of gas adsorbed on the solid surface at different relative pressures, and then calculate the monolayer adsorption amount of the sample based on the Brunaue-Emmett-Teller (BET formula).
[0093] Material tap density test method: The tap density is tested using the Quantachrome AutoTap tap density meter.
[0094] Table 1 Physical and chemical properties of hard carbon negative electrode materials of Examples and Comparative Examples
[0095] <![CDATA[Apparent density of the material / g / cm 3 > <![CDATA[Specific surface area of material / m 2 / g]]> Example 1 0.84 6.5 Example 2 0.86 6.4 Example 3 0.82 8.2 Example 4 0.85 6.7 Example 5 0.89 7.9 Example 6 0.80 4.5 Example 7 0.81 5.3 Example 8 0.82 9.3 Example 9 0.85 6.2 Example 10 0.83 7.8 Comparative Example 1 0.78 4.8 Comparative Example 2 0.86 6.1 Comparative Example 3 0.81 21.4 Comparative Example 4 0.84 6.3 Comparative Example 5 0.83 8.4
[0096] Experimental Example 2
[0097] Half-cells were prepared using the hard carbon negative electrode materials prepared in Examples 1-10 and Comparative Examples 1-5, and the electrochemical performance of the half-cells was tested. The test results are shown in Table 2.
[0098] In the half-cell, the obtained silicon-oxygen negative electrode material, conductive carbon black SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed together in a mass ratio of 90:2:2:6 with water as a dispersant to prepare a slurry. The obtained slurry is coated on a copper foil current collector, and then dried, rolled, and cut to obtain a negative electrode sheet.
[0099] The half-cell uses metallic sodium as the negative electrode, with a voltage range of 0.005-1.5V. During discharge, the current density is first discharged at a constant current of 0.05C to 0.05V, then discharged at a constant current of 0.2C to 0.005V, left to stand for 20 minutes, and charged at a constant current of 0.05C to 1.5V.
[0100] Table 2: Electrochemical performance of half-cells
[0101]
[0102]
[0103] It can be seen from the data in Table 1 that one or more of the parameters of the hard carbon negative electrode materials provided in Comparative Examples 1 to 5 are not within the scope of the present invention, and the half-cell electrochemical performance of these hard carbon negative electrode materials is poor. The half-cell electrochemical performance of the hard carbon negative electrode materials provided in Examples 1 to 10 is better.
[0104] From the experimental data of Examples 1, 2, 8 and Comparative Examples 2 and 3, it can be seen that when the concentration of NaOH is lower than 0.5 mol / L or higher than 3 mol / L, the electrochemical performance of the battery is poor. The possible reason is that the concentration of NaOH is too low to dissolve impurities in the biomass raw materials; when the concentration of NaOH is higher than 3 mol / L, the pore-forming properties of the strong base will significantly increase the specific surface area of the hard carbon material, and a larger SEI film will be generated when sodium is first embedded, resulting in a decrease in the first cycle efficiency. Therefore, the present invention limits the concentration of NaOH to 0.5 mol / L to 3 mol / L for the best.
[0105] From the data of Examples 1, 3, 9, 10 and Comparative Examples 4 and 5, it can be seen that when the concentration of Na3PO4 is lower than 0.1 mol / L or higher than 0.5 mol / L, the electrochemical performance of the battery is poor. The possible reason is that when the concentration of Na3PO4 is too low, the amount of P heteroatom doping on the surface of the hard carbon material is reduced, the ionic conductivity is reduced, and thus its rate performance is reduced; when the concentration of Na3PO4 is too high, the P heteroatom content is too high, resulting in an unstable structure of the hard carbon material, which reduces its cycle performance. Therefore, the present invention limits the concentration of Na3PO4 to 0.1 mol / L to 0.5 mol / L for the best.
[0106] From the data of Example 1 and Comparative Example 1, Figures 1 to 3 It can be seen that the present invention improves the first sodium removal capacity of the half-cell by 10% (289.9 / 263.7*100%-1=10%) and the first coulombic efficiency of the half-cell by 6.3% (90.39 / 85.06*100%-1=6.3%) by pretreating the hard carbon source. Although the capacity retention rate of the half-cell is slightly reduced after 100 cycles, the capacity retention rate at high current density is increased by 54% (86.84 / 56.55*100%-1=54%). Therefore, the present invention uses a mixed solution of Na3PO4 and NaOH to treat the hard carbon source, which effectively improves the first cycle efficiency and capacity of the hard carbon, and the Na formed on the surface of the hard carbon +Defects and P heteroatom doping structures enhance the Na + The transmission rate is increased, and the rate performance of the hard carbon negative electrode is improved, thus obtaining a sodium ion battery hard carbon negative electrode material with high first-cycle efficiency and capacity as well as high rate performance.
[0107] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0108] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0109] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0110] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0111] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are included: S1, prepare a mixed solution of Na3PO4 and NaOH; S2, pretreating the hard carbon source with the mixed solution; S3, solid-liquid separation, washing the pretreated hard carbon source with a washing liquid; S4. The washed hard carbon source is subjected to high-temperature pyrolysis to obtain a hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S1, in the mixed solution, the concentration of Na3PO4 is 0.1-0.5 mol / L, and the concentration of NaOH is 0.5-3 mol / L.
3. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S2, the hard carbon source is preliminarily carbonized coconut shell biomass.
4. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S2, the pretreatment temperature is 30 to 100°C, and the pretreatment time is 2 to 24 hours.
5. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S3, the washing liquid is deionized water or pure water.
6. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S4, the high temperature pyrolysis temperature is 900-1500° C., the time is 2-6 hours, and the heating rate is 1-5° C. / min.
7. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step S4, nitrogen or argon is used as a protective gas throughout the high-temperature pyrolysis process.
8. A hard carbon negative electrode material for a sodium ion battery, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7.
9. A sodium ion battery negative electrode, characterized in that: Including the sodium ion battery hard carbon negative electrode material as described in claim 8.